Effects of Helicobacter pylori and liver cirrhosis on gastric mucosal hexosamine concentrations - Murat ARABACI; Tankut KÖSEOĞLU; Yücel ÜSTÜNDAĞ; Kamer ASLAMİRZA and Erdal ESKİOĞLU (Turkish Journal of Gastroenterology, 2019)
-